Processing of discarded refrigerators in The Netherlands - Stoop, Mat L.M (Technovation)
The authors suggest that the re-design of refrigerators in The Netherlands could be modified to cover re-processing of discarded refrigerators with a view to ecological considerations. The work is based on a case study.